THE TUNA LiVfi-BAlT FISHERY OF MINICOY ISLAND - Jones, S (Indian Journal of Fisheries, 2016)
Specimens of fishes of Minicoy Island including tuna live-bait fishes were being collected for the last four years through the co-operation of the Medical Officers stationed there. In October 1956, Mr. M. Kumaran, Laboratory Attender of this Research Station, was sent there to collect specimens of fishes and information on the fishing industry. In February 1958 I was able to visit the Island on board the Research Vessel ’ Kalava’ of the Indo-Norwegian Project and personally see the tuna bait fishery and check the information collected.